Influence of high risk HPV genotype on colposcopic performance: A large prospective study demonstrates improved detection of disease with ZedScan I, particularly in non-HPV 16 patients. (April 2017) - Macdonald, Madeleine C.; Brown, Brian H.; Lyon, Rachel E.; Healey, T. Jamie; Palmer, Julia E.; Tidy, John A.
Abstract: Objective: To assess the influence of high-risk Human Papilloma Virus (hrHPV) genotyping on the detection of high-grade disease (CIN2+) using colposcopic impression both with and without electrical impedance spectroscopy (ZedScan I ) as an adjunct. Study design: A prospective cohort of women with a known hrHPV genotype referred to a single colposcopy service. Results: 839 women underwent colposcopy and ZedScan I examination. 613 women were referred with abnormal cytology; 411 (67%) with low-grade dyskaryosis (67%) and 202 (33%) with high-grade dyskaryosis. 187 were referred with persistent hrHPV but negative cytology. 35 were attended for follow up and 4 for a clinical indication. 159 (19%) women were positive for HPV16 only; 54 (6%) with HPV18 only, 443 (53%) women were positive for hrHPV other types (HPV O). 183 (22%) were positive for multiple hrHPV genotypes. CIN2+ was present in 170 (84.2%) of high-grade and 69 (16.7%) of low-grade cytology referrals. Colposcopy was better at detecting HPV16 associated CIN2+ than that associated with HPV18 or HPV O (86.9% vs 79.7%, p = 0.0191). ZedScan I increased the detection of CIN2+ from 85.6% to 96% irrespective of hrHPV genotype status (p < 0.0001). Conclusion: The use of an electrical impedance spectroscopic device (ZedScan I ) increases detection of CIN2+ irrespective of hrHPV genotype.